PORTALS IN PANES: THE ART AND SCIENCE OF SPELLBOUND SPECILUM FOR INTERACTIVE LEARNING AT SCHOOLS. - N, Lakshminarayan; G L, Manjunatha; K N, Anuradha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper, Portals in Panes: The inclusion of the Spellbound Specilum prototype using AI in educational institutions for learning activities will enhance the Interactive Learning Process. The traditional classroom interactions can be turned into tech-bound communicator by combining a transparent digital display with a two-way mirror, through which can get real-time information dynamically. The student engagement & learning experiences can be intensified by utilizing voice recognition and augmented reality techniques. This improvises learning through interactive lessons, multimedia presentations etc., The complex concepts can be made more accessible and engaging by active learning and collaboration encouraged by Spellbound Specilum which is found by observation. Spellbound Specilum offers a future view of interactive learning technologies by serving both as a practical tool and beautify the classroom when it is mixed with art and science. The outcome of the research is that Spellbound Specilum can bring major changes in the current educational methods by providing deep learning capabilities that deliver distinct educational needs and improvise the learning experience completely.